Evaluation of the relationship between vitamin D levels and emerge delirium in children who had tonsillectomy and/or adenoidectomy - Nagehan Ümit Karacan; Sinan Yılmaz; Mustafa Yılmaz (National Scientific Medical Center, 2023)
Background: Pediatric emergence delirium is a general complication of anesthesia with an incidence of 2-80%. Although its etiology is not clearly known, it has been shown that anesthesia method, surgical procedure, and child and parent anxiety may cause the emergence delirium. The relationship between vitamin D levels and emerge delirium in children who underwent tonsillectomy and/or adenoidectomy has not been investigated before Aim:  In this context, this study was carried out to evaluate the relationship between vitamin D levels and emerge delirium in children who underwent tonsillectomy and/or adenoidectomy. Material and methods: The study population consisted of children between the ages of 2 and 10, ASA I-II and were scheduled to have elective adenoidectomy and/or tonsillectomy under general anesthesia. All children (n=97) were evaluated for anxiety with the modified Yale Preoperative Anxiety Scale (m-YPAS) before surgery. Children with serum 25(OH)D levels<12 ng/ml and ≥12 ng/ml were categorized as group 1 (n=50) and group 2 (n=47). All children were evaluated for delirium with the Pediatric Anesthesia Emergence Delirium (PAED) scale. The face, legs, activity, cry, consolability (FLACC) scale was used in the evaluation of postoperative pain in children who could not express themselves verbally. Results: The mean serum 1.25(OH)2D3 level was higher, albeit insignificantly, in group 1 than in group 2. There was no significant difference between the two groups in terms of emerge delirium, preoperative anxiety, postoperative pain and analgesia. Conclusion: Vitamin D deficiency does not affect the incidence of emergence delirium in children. Vitamin D level does not relate to preoperative anxiety and postoperative pain.